Efektivitas Terapi Spiritual Emotional Freedom Technique (Seft) Terhadap Penurunan Tekanan Darah Pada Lansia dengan Penderita Hipertensi - Soleha, Nunu; Adawiyah, Siti Robeatul; Ashari, Siti Bunga; Safitri, Nurul; Linda, Linda; Latif, Mohamad Sohibul (Pustaka Galeri Mandiri, 2025)
Hypertension is a health problem with a high prevalence in the elderly and is at risk of causing serious complications. The management is not only pharmacological, but also non-pharmacological, one of which is the Spiritual Emotional Freedom Technique (SEFT), which is a mind-body therapy-based complementary therapy that combines acupressure point stimulation with prayer for relaxation, stress reduction, and stabilization of blood pressure. This study uses the literature review method by searching articles through Google Scholar, Garuda, Science Direct, and Semantic Scholar databases, with a publication range of 2019-2025. Of the 505 articles found, 8 met the inclusion criteria for analysis. The study showed that the application of SEFT therapy was proven to be effective in lowering systolic and diastolic blood pressure in hypertensive elderly people. This effect is obtained through a reduction in emotional stress, increased calmness, as well as the stimulation of endorphins hormones that help relax blood vessels. SEFT therapy has been shown to be effective as a nonpharmacological intervention in helping to lower blood pressure in elderly people with hypertension. This therapy can be used as a supportive alternative to pharmacological therapy, and has the potential to improve the quality of life of the elderly.